Strengthening Organizational Brand Image Through The Sore Ceria Broadcast Program On Pro 2 Rri Bengkulu - Arini Jusiati; Dilmai Putra; Martha Heriniazwi Dianthi (Journal of Multidisciplinary Research, 2026)
This study aims to analyze how the Sore Ceria broadcast program on PRO 2 RRI Bengkulu contributes to strengthening the organizational brand image of Radio Republik Indonesia as a public broadcasting institution. Radio as a conventional mass media still plays an important role in delivering information, entertainment, and education to society, especially at the local level. However, the development of digital media requires radio institutions to adapt through broadcast program strategies that are relevant to the needs of audiences, particularly young listeners. This research applies a descriptive qualitative approach with data collection techniques including in depth interviews, broadcast observations, and documentation. The research informants consist of the program producer, announcer, and a local small business owner who has participated as a guest in the program. Data analysis was conducted using a framing model consisting of four elements, namely defining problems, diagnosing causes, making moral judgment, and providing treatment recommendations. The findings indicate that the Sore Ceria program frames issues related to youth and local entrepreneurs in the context of developing potential, creativity, and independence in the digital era. The program presents inspirational speakers, provides interactive dialogue opportunities, and delivers practical solutions related to education, motivation, and business development. Through a dialogic and constructive communication approach, the program functions not only as a source of entertainment but also as a medium for community empowerment. This strategy contributes to shaping the image of RRI Bengkulu as an adaptive, educational, and community oriented public broadcasting institution.